2017
DOI: 10.18488/journal.aefr.2017.712.1256.1302
|View full text |Cite
|
Sign up to set email alerts
|

Economic Liberalization and Economic Growth: An Empirical Analysis of Pakistan

Abstract: Article History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 123 publications
(175 reference statements)
3
15
0
Order By: Relevance
“…The short‐run relationship between financial innovation and the measures of money demand are significantly positive as a 1% increase in the value of financial innovation transactions leads to a 26.5%, 71.90% and 61.60% increase in M1, M2 and M3, respectively. This is consistent with the findings of Hafer and Kutan (2003) in the Philippines, Adil et al (2020) in India, Hye (2009) in Pakistan, Cho and Miles (2007) in Korea, and Akosah et al, (2017), Mannah‐Blankson and Belyne (2004) and Insah et al (2013) in Ghana. The results indicate that the impact of financial innovation is higher on broad money and in the long run than the short run and could imply that financial innovation increases the velocity money demand.…”
Section: Resultssupporting
confidence: 89%
“…The short‐run relationship between financial innovation and the measures of money demand are significantly positive as a 1% increase in the value of financial innovation transactions leads to a 26.5%, 71.90% and 61.60% increase in M1, M2 and M3, respectively. This is consistent with the findings of Hafer and Kutan (2003) in the Philippines, Adil et al (2020) in India, Hye (2009) in Pakistan, Cho and Miles (2007) in Korea, and Akosah et al, (2017), Mannah‐Blankson and Belyne (2004) and Insah et al (2013) in Ghana. The results indicate that the impact of financial innovation is higher on broad money and in the long run than the short run and could imply that financial innovation increases the velocity money demand.…”
Section: Resultssupporting
confidence: 89%
“…Hence, exports play a vital role in promoting economic growth in the country. This result is similar to the results obtained by Tyler (1981), Balassa (1985), Krueger (1990), Singupta and Espana (1994), Shirazi and Abdul-Manap (2004), Alhajhoj (2007), Hye andBel Haj Boubaker (2011), andSaad (2012).…”
Section: Johansen Cointegration Test Resultssupporting
confidence: 92%
“…Moreover, many empirical studies, including Tyler (1981), Balassa (1985), Ram (1987), Krueger (1990), Khan and Saqib (1993), Sengupta and Espana (1994), AlYousif (1997), Shirazi and Abdul-Manap (2004), Abou-Stait (2005), Alhajhoj (2007), Hye andBoubaker (2011), Saad (2012), Malhotra and Kumari (2016) have tested the role of exports in economic growth and found that there was a positive relationship between exports and economic growth. Besides, trade liberalization has also been found to have a positive effect on economic growth, according to Heitger (1987), Edwards (1992), Harrison (1996), Greenaway (1998), Onafowora and Owoye (1998), Greenaway et al (2001), Utkulu and Ozdemir (2004), Buehler et al (2011), andMercan et al (2013).…”
Section: Previous Studiesmentioning
confidence: 99%
“…According to the study, higher human capital levels, a stable macroeconomic environment, and good institutions can reduce the negative and insignificant effects of international financial integration. Similarly, Hye and Wizarat (2013) used the ARDL method to show that financial integration has no significant long-term influence on Pakistani economic growth. For both models, only trade openness is found to be a significant variable for economic growth in the short run.…”
Section: Empirical Results and Analysismentioning
confidence: 99%